Sexual and reproductive well-being of teenage mothers in a South African township school - Nomvuyo Nkani; Deevia Bhana (South African Journal of Education, 2016)
Research addressing the sexual health and reproductive rights of pregnant teenagers and teenage mothers is growing, although attention to the sexual well-being of young mothers who are already in school remains limited. This omission places teenage mothers at risk, who may be susceptible to repeated pregnancies that may compromise their well-being and educational outcomes. By drawing on a qualitative study, we focus on young mothers' sexual relationships and their knowledge and choice of contraceptive methods, as well as their accessibility to them. In this paper, we ask how sexual and reproductive well-being is constructed in relation to knowledge, choice and accessibility to contraceptive methods. While the study found that schooling was constructed as vital to economic empowerment, teenage mothers' aspirations were compromised by limited contraceptive knowledge and choices, and enduring patterns of gender inequalities within relationship dynamics. Effective interventions require attention to a comprehensive understanding of sexual health, which includes a focus on gender and relationship dynamics, as well as knowledge of and access to contraceptive methods. Accessibility to all methods of contraceptive use remains vital in all health centres. Community health workers need to engage better with young mothers so as to support their reproductive well-being.